2019
DOI: 10.1111/ajt.15233
|View full text |Cite
|
Sign up to set email alerts
|

Shared alloimmune responses against blood and transplant donors result in adverse clinical outcomes following blood transfusion post–renal transplantation

Abstract: De novo HLA donor specific antibodies (DSA) following transplantation are associated with alloimmune injury and allograft failure. Blood transfusions are allogeneic, and when given posttransplant (PTBT) they may independently increase the risk of HLA antibody development. This study aims to analyse the development of HLA transfusion specific antibodies (TSA) to blood donors of transfusions given post-transplant and examine the impact on clinical outcomes. 244 blood donors of transfusions received by 86 transpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
37
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(56 citation statements)
references
References 33 publications
(53 reference statements)
2
37
2
Order By: Relevance
“…Additionally, there is a theoretical risk that the use of CCP may treat or prevent COVID‐19 disease in a way that mitigates the native humoral immune response, leaving these individuals vulnerable to subsequent reinfection 19 . Furthermore, for solid organ transplant recipients in particular, there is some evidence of a risk of developing donor‐specific antibodies (and subsequent antibody mediated rejection) after receiving allogeneic blood products, 20 but this risk is likely very low with CCP given the expected minimal HLA antigen load in a single‐donor plasma product.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, there is a theoretical risk that the use of CCP may treat or prevent COVID‐19 disease in a way that mitigates the native humoral immune response, leaving these individuals vulnerable to subsequent reinfection 19 . Furthermore, for solid organ transplant recipients in particular, there is some evidence of a risk of developing donor‐specific antibodies (and subsequent antibody mediated rejection) after receiving allogeneic blood products, 20 but this risk is likely very low with CCP given the expected minimal HLA antigen load in a single‐donor plasma product.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a more recent study by Hassan et al 20 found posttransplant blood transfusion to be associated with a higher risk of allograft failure, all rejection, and de novo DSA formation. Their study also suggested that posttransplant blood transfusion could evoke de novo DSAs.…”
Section: Discussionmentioning
confidence: 78%
“…These reports had conflicting results in terms of the risk for acute rejection and graft and patient survival. [16][17][18][19][20] Therefore, we aimed to evaluate whether the transfusion of blood products was indeed associated with an increased risk for acute rejection, graft loss, or death by any cause in nonsensitized kidney transplant recipients on maintenance immunosuppressive therapy.…”
mentioning
confidence: 99%
“…Although blood transfusion pre-transplantation is generally avoided due to the risk of sensitization, there remains debate on its impact [ 12 ]. The effect of transfusion post transplantation (with a functioning graft) is less well studied but is thought to increase the risk of developing a DSA [ 19 ]. Interestingly, the incidence of de novo DSA development in this cohort was no higher with EBT than without it.…”
Section: Discussionmentioning
confidence: 99%